(untitled) (Research, Society and Development, 2021)
Introduction: Multicanal vertigo is a rare disorder and vestibular rehabilitation is one of the treatment methods, aiming to stimulate the neuroplasticity of the central nervous system. Objective: To examine the effect of a vestibular rehabilitation program on static balance and postural stability in an individual with vertigo. Case report: Male patient, 58 years old, with clinical diagnosis of benign paroxysmal positional vertigo for 12 years, with frequent episodes of vertigo, loss of balance and falls. The assessment of balance and postural stability were performed using the Romberg test with eyes open and closed, on a S-Plate v.14 – Medicapteurs – France, force platform, analysing data at a risk of p<0.05 level. After the Epley´s Maneuver, the vestibular rehabilitation program was started. It consisted of Cawthorne-Cooksey vestibular exercises, the Brandt-Daroff modified maneuver, and the Norre´s vestibular habituation training, twice a week, for a total of 10 sessions. Results: The tests performed with eyes open, did not show a statistically significant difference between pre and post treatment. However, in the stabilometric analysis, the wave width, the mean deviation, and the mean speed in the anteroposterior (A/P) and latero-lateral (L/L) displacements in mm/s, as well as the postural stability for the eyes closed tests had a statistically significant improvement. Conclusion: Vestibular rehabilitation was effective in improving static balance and postural stability in this case report, scientifically corroborating the importance of the chosen rehabilitation method as a viable option for the treatment of peripheral vestibulopathy.